The Implementation of Problem-Based Learning Models using Google Sites to Improve Students’ Problem Solving Skills on the Topic of Electrical Safety System - Fathiah Damri Said; Yus Rama Denny; Asep Hidayat (Gravity : Jurnal Ilmiah Penelitian dan Pembelajaran Fisika, 2022)
This study aims to obtain an overview of the effectiveness of the application of problem-based learning models assisted by google sites to improve students' problem solving skills on direct current electricity topic, especially electrical safety system subtopic. Pre-experiment method with one group pretest-posttest design was conducted in this study. The research subjects consisted of 31 students of 12th grade science in the first semester of the 2022/2023 academic year at a public high school at Tangerang regency. The research instruments consisted of 2 structured questions for the problem solving ability test where each question contained indicators of targeted problem solving skills, namely: identifying problems, describing problems with physics quantities, plan the solutions, execute the solutions, and evaluating the resultsof problem solving. This study was conducted in three stages: 1) the preliminary study includes literature review, field study, developing google sites for learning purpose, preparing the lesson plans and the problem-solving worksheets, and developing the instrument tests; 2) the implementation stage includes the implementation of PBL in the classroom; 3) the final stage includes analyzing data and presenting the results of the study. According to the data, it can be concluded that the application of the PBL model in learning the topic of electrical safety systems can improve students' problem solving skills, indicated by the average N-gain score of students' problem solving skills of 0.91 with the category of improvement is high.